Pengaruh Model Keseimbangan Umum terhadap Distribusi Kesejahteraan Masyarakat di Indonesia - Hutauruk, Elisabeth Tamara Ratu; Batubara, Nidia Izmi Azizah; Fadilah, Tri Ayu; Syakinah, Wanda (Alpatih Harapan Semesta, 2025)
This study aims to analyze the impact of the general equilibrium model (CGE) to be calculated on the happiness distribution in Indonesia. The study used a qualitative method by reviewing documents and described analysis, using secondary data from university magazines and official organizations such as BPS and OECD in 2018-2024. The results show that the CGE model can simulate the impact of economic policies on resource allocation and happiness distribution. The policy has been shown that food supply and cash transfer reduces income inequality without affecting the global economic efficiency. However, the limits occurred in the war against the imperfection of the market and complicated social environmental factors. The meaning of emphasizing the importance of integrating social justice in the CGE model to ensure that public policies in Indonesia are more comprehensive, adaptable and fairer.